Konsep Ruang Siber dalam Perspektif Hukum Modern: Menimbang Ulang Kedaulatan, Yurisdiksi, dan Subjek Hukum di Era Digital - Gilang Rizki Aji Putra (BULETIN ADALAH, 2020)
Cyberspace has created a new dimension of existence that transcends the physical boundaries underlying modern law. This article examines cyberspace from theoretical and practical perspectives within contemporary legal frameworks, focusing on sovereignty, jurisdiction, and legal subjects. Using normative legal research combined with philosophical and comparative approaches, the study finds that territoriality rooted in the Peace of Westphalia is no longer effective in governing borderless digital environments. Unilateral jurisdictional claims create sovereignty conflicts and legal uncertainty, while new digital entities challenge traditional legal subject definitions. Modern law must adopt functional sovereignty and structured jurisdictional pluralism.   Keywords: Cyberspace, Digital Sovereignty, Jurisdiction, Modern Law, Territoriality